Por vozes nunca dantes ouvidas : a viragem pós-colonial nas ciências humanas - Dewulf, Jeroen (2014)
This article focuses on Post-Colonialism. We start with an analysis of important changes in anthropology in consequence of the colonial era and the so called "the others speak back"-movement. We then switch to Edward Said and his revolutionary work Orientalism (1978), the real beginning of Post-Colonialism as an academic topic. The importance of postcolonial studies is illustrated by two major works: Said’s Culture and Imperialism (1993) and Homi Bhabha's The location of culture (1994).